Narrative Means to Journalistic Ends A Narratological Analysis of Selected Journalistic Reportages - Berning, Nora.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2011)
Nora Berning grasps the narrative potential of journalistic reportages via a set of narratological categories. Spurred by an interdisciplinary framework, she builds on transgeneric narratological research and shows that journalistic reportages can be described, analyzed, and charted with categories that originate in structuralist narratology. The author spells out minimal criteria for particular types of reportages, and challenges the argument that journalism and literature have distinct, non-overlapping communicative goals. By showing that the reportage is a hybrid text type that seeks to inform, educate, and entertain, this study advances a re-conceptualization of journalism and literature as two fields with permeable borders. The book is written for researchers and students in the fields of journalism, media, communications, and literary theory.
Keywords: Social sciences; Sociology; Social Sciences; Sociology; Sociology